Physico-Chemical Changes In Sugarcane (Saccharum Officinarum Var. Yellow Cane) And The Extracted Juice During Development, Maturation And Postharvest Treatments Upon Storage - M. Qudsieh, Hanan Yassin (2001)
A study was conducted to determine the physico-chemical changes between different portions (top, middle, and bottom) of sugarcane at different maturity stages (between 3 and 10 months from planting). The variety used was Saccharum officinarum var. Yellow cane. The parameters analysed were weight, diameter, yield, total colour of juice, total soluble solids (TSS), pH, titratable acidity, sugar content (sucrose, glucose, fructose), tannin, chlorophyll and polyphenol oxidase (PPO) activity. The weight, diameter, total soluble solids (TSS) and sucrose content increased significantly (P<O.01 ) for sugarcane from all portions (top, middle and bottom) until the end of maturity stage. On the other hand, titratable acidity (TA) values, pH, juice yield, glucose, fructose contents, tannin, chlorophyll and PPO decreased significantly (P<O.0 1 ) during maturity. Significant differences were also detected in all the parameters between the different portions during maturity. Results obtained indicated that there were significant decreases (P<0.01) in tannin and chlorophyll contents during maturity.